1978
DOI: 10.4141/cjas78-042
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Digestibility Studies With Growing–finishing Pigs Receiving Whole Barley or Ground Barley by Various Feeding Methods

Abstract: BEAMES, R. M. AND NGwrP"{, T. N. 1978. Growth and digestibility studies with growing-finishing pigs receiving whole barley or ground barley by various feeding methods. Can. J' Anim. Two growth trials and one digestibility trial with growing-finishing pigs are reportid. In each growth trial, three groups of six barrows and three groups of six giits were placed Jn each of the four dietary treatments of barley plus 15% soybean meal fromapprox.23 kg body weight to approx' 84 kg body weight' The four treatments co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…However, the pigs fed the HF diet had significantly higher OM, NSP, NCP, and cellulose digestibility in week 6 than in week 12. This has also been found in a previous study where younger pigs were found to have higher ATTD of DM compared with older pigs on barley-based diet (Beames and Ngwira, 1978). Angelis et al (2015) reported that Bacteroides, Porphyromonas, and Prevotella spp., which are related to DF degradation, were decreased due to barley β-glucan.…”
Section: Discussionsupporting
confidence: 82%
“…However, the pigs fed the HF diet had significantly higher OM, NSP, NCP, and cellulose digestibility in week 6 than in week 12. This has also been found in a previous study where younger pigs were found to have higher ATTD of DM compared with older pigs on barley-based diet (Beames and Ngwira, 1978). Angelis et al (2015) reported that Bacteroides, Porphyromonas, and Prevotella spp., which are related to DF degradation, were decreased due to barley β-glucan.…”
Section: Discussionsupporting
confidence: 82%